2009
DOI: 10.1194/jlr.m800384-jlr200
|View full text |Cite
|
Sign up to set email alerts
|

Trafficking pathways of mycolic acids: structures, origin, mechanism of formation, and storage form of mycobacteric acids

Abstract: Mycolic acids, the hallmark of mycobacteria and related bacteria, are major and specific components of their cell envelope and essential for the mycobacterial survival. Mycobacteria contain structurally related long-chain lipids, but the metabolic relationships between these various classes of compounds remain obscure. To address this question a series of C 35 to C 54 nonhydroxylated fatty acids (mycobacteric acids), ketones, and alcohols structurally related to the C 70-80 dicyclopropanated or diethylenic myc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 40 publications
0
12
0
Order By: Relevance
“…The MALDI data suggested that TAG was the main compound of the secretion as no other spectra were detected in the sample. The two series of peaks in the TAG spectrum of M. smegmatis further indicated two different types of TAGs due to a combination of fatty and mycolic acids with different chain lengths as described for M. brumae (Rafidinarivo et al, 2009).…”
Section: Effects Of Hypoxic Culture Conditions On Metabolite Levels (mentioning
confidence: 53%
See 1 more Smart Citation
“…The MALDI data suggested that TAG was the main compound of the secretion as no other spectra were detected in the sample. The two series of peaks in the TAG spectrum of M. smegmatis further indicated two different types of TAGs due to a combination of fatty and mycolic acids with different chain lengths as described for M. brumae (Rafidinarivo et al, 2009).…”
Section: Effects Of Hypoxic Culture Conditions On Metabolite Levels (mentioning
confidence: 53%
“…5b). The fingerprint of the molecular ion peaks was typical for MALDI spectra of TAG as seen through comparison with TAG spectra of M. brumae (Rafidinarivo et al, 2009). The MALDI data suggested that TAG was the main compound of the secretion as no other spectra were detected in the sample.…”
Section: Effects Of Hypoxic Culture Conditions On Metabolite Levels (mentioning
confidence: 83%
“…Compounds structurally related to mycolic acids are found in significant amounts in mycobacteria. These compounds include long chain acids, alcohols and also ketones [35]. Mycolic acids represent important components of the cell envelope of mycobacteria.…”
Section: Discussionmentioning
confidence: 99%
“…Mycobacterial cells were treated three times with mixtures of chloroform and methanol according to standard protocols (Constant et al, 2002;Rafidinarivo et al, 2009). The organic phases were pooled, dried and weighed for quantification.…”
Section: -Dementioning
confidence: 99%